The Cincinnati kid [videorecording (DVD)]. - Robinson, Edward G., 1893-1973; Ann-Margret, 1941-; McQueen, Steve, 1930-1980; Jewison, Norman, 1926- (Warner Home Video (distributor), 2005)
The Cincinnati Kid is a small time poker player eager to take his chances in high-stakes poker. He gets his chance. Regal, ruthless Lancey Howard, the elite gambler called the Man, accepts the Kid's challenge. This is a taut exploration of back-room gaming, building suspense with each turn of a card.